The benefits and limitations of farm equipment supply subsidy: Experiences and lessons from Senegal - Tadesse, Getaw; Goundan, Anatole; Sarr, Saer (African Association of Agricultural Economists, 2019)
Using household level data collected from cereal based farming systems of Senegal, we examined the prospects and challenges of the Senegalese equipment supply subsidy program. Because of the design of the program—being procured and supplied by the government—we argue that the effect of this program on adoption of improved farm equipment depends on the supply and price benefits as well as the relative importance of ownership to access farm equipment. To empirically support this argument, we assessed the benefits of the subsidy in creating markets and reducing prices and its effectiveness in motivating farmers to use modern farm equipment. Our analyses indeed revealed that though the number of farmers benefited from the subsidy is small, the program has significantly improved the adoption of farm equipment drawn by animals mainly due to its market creation benefit. This has been further confirmed by the qualitative response of farmers who appreciated the quality of the equipment being supplied by the program. However, the effect of subsidy on machinery use is insignificant as it doesn’t provide support to those farmers who primary depend on rental services. The price advantage created by the subsidy program is not as such significant either. Farm equipment purchased from the program and the open market appear to have closely similar prices.